Negotiating Curriculum in a Critical Pedagogy - Peter G. Malvicini (Adult Education Research Conference, 2001)
Through critical reflection and dialog on experiences in participatory planning, curricula that values participatory democracy can be fostered. An empirical study, using participatory research, demonstrates that students and faculty can move toward a more critical and inclusive pedagogy by reflecting on cultural diversity.